2006
DOI: 10.1007/s10526-006-9047-z
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of shore fly Scatella stagnalis to five entomopathogenic nematode strains in bioassays

Abstract: The shore fly, Scatella stagnalis (Falle´n) (Diptera: Ephydridae) is an important insect pest of greenhouse crops. We evaluated two different Spanish isolates of entomopathogenic nematodes, Steinernema feltiae (Filipjev) (Rhabditida: Steinernematidae) and Steinernema arenarium (Artyukhovsky) (Rhabditida: Steinernematidae), and two commercially available strains, Steinernema feltiae (Nemaplus Ò ) and Heterorhabditis bacteriophora (Poinar) (Rhabditida: Heterorhabditidae) (Nematop Ò ) against shore flies. In test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
2
2
0
1
Order By: Relevance
“…Similar results have been obtained by other authors who confirmed the lack of a correlation between penetration rate and host mortality (Gaugler et al 1990;Epsky and Capinera 1994). The results obtained in this study for the reduction of the penetration rate of EPNs with increasing dose was also reported by Selvan et al (1993) in wax moth G. mellonella, by Cabanillas (2003) in the boll weevil Anthonomus grandis, and by Morton and Garcia-del-Pino (2007) in the shore fly Scatella stagnalis. Caroli et al (1996) showed that the penetration rate in heterorhabdı´tids is lower than in steinernematids infecting different insects.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similar results have been obtained by other authors who confirmed the lack of a correlation between penetration rate and host mortality (Gaugler et al 1990;Epsky and Capinera 1994). The results obtained in this study for the reduction of the penetration rate of EPNs with increasing dose was also reported by Selvan et al (1993) in wax moth G. mellonella, by Cabanillas (2003) in the boll weevil Anthonomus grandis, and by Morton and Garcia-del-Pino (2007) in the shore fly Scatella stagnalis. Caroli et al (1996) showed that the penetration rate in heterorhabdı´tids is lower than in steinernematids infecting different insects.…”
Section: Discussionsupporting
confidence: 92%
“…(TF135) had a penetration rate similar to that of H. bacteriophora (TF19). This similar penetration rate for steinernematids and heterorhabditids was also found by Garcı´a-del-Pino and Morton (2005) in neonate larvae of the flatheaded rootborer C. tenebrionis (Buprestidae) and by Morton and Garcia-del-Pino (2007) in S. stagnalis larvae.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Dit kwam omdat de aaltjes niet goed konden overleven in de steenwol. Morton & del Pino (2007) hebben de effectiviteit van 5 verschillende insectparasitaire aaltjes tegen oevervliegen bekeken en vonden van alle soorten een hoge activiteit tegen oevervliegen in laboratoriumproeven. Ze hebben echter geen veldproeven gedaan.…”
Section: Insectparasitaire Aaltjesunclassified
“…In Spain and UK, some preliminary studies were conducted on the identification of this pest, its host plants, symptoms, sources and suitable growing conditions [1,2,3]. In China, only Hu Xue-you carried out taxonomical study of ephydridae in China [4].…”
Section: Introductionmentioning
confidence: 99%